Metoda wektorów nośnych na tle innych metod wielowymiarowej analizy danych - Trzęsiok, Michał (Support vector machines in comparison to other methods of multivariate statistical analysis, 2006)
Support vector machines (SVM) belong to a group of rapidly developing methods of multivariate statistical analysis. The main goal of this article is to compare the SVMs to other classification methods (e.g. Linear Discriminant Analysis, k-Nearest Neighbour Classification, Classification Trees) in terms of classification error generated by the final model. The analysis was conducted on some real and artificial benchmarking data sets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 536-542